2012
DOI: 10.1007/s12282-012-0406-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hypofractionated and conventionally fractionated whole-breast irradiation for early breast cancer patients: a single-institute study of 1,098 patients

Abstract: HF-WBI is superior to CF-WBI in terms of acute skin reaction and has the same short-term efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 12 publications
4
17
0
Order By: Relevance
“…Treatment costs for CFRT were US$5405 in patients with negative margins and US$5649 in patients with positive margins. Thus, treatment costs were almost one-third lower for HFRT for all patients [16]. Other reviews or articles reported similar results.…”
Section: Costs and Conveniencesupporting
confidence: 56%
See 3 more Smart Citations
“…Treatment costs for CFRT were US$5405 in patients with negative margins and US$5649 in patients with positive margins. Thus, treatment costs were almost one-third lower for HFRT for all patients [16]. Other reviews or articles reported similar results.…”
Section: Costs and Conveniencesupporting
confidence: 56%
“…In the 2.5e3.0 Gy per fraction subgroup, 9 studies with 9011 patients were included in the meta-analysis [10e13, 16,24,25,28,38,39], pooled RR indicated that HFRT were with comparable local regional recurrence rate in comparison with CFRT [RR ¼ 1.03, 95% CI (0.87, 1.23), P ¼ 0.72]. In the 3.01e3.33 Gy per fraction subgroup, meta-analysis of 2 RCTs with 2435 patients showed that there was no significant difference between HFRT and CFRT [RR ¼ 0.89, 95% CI (0.67, 1.18), P ¼ 0.41] [11,13].…”
Section: Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…These trials, with median follow-up times of 9 to 12 years, have demonstrated that hypofractionated radiotherapy is associated with equivalent local control compared to standard fractionation and a similar or lower rates of late effects on breast and also in the surrounding tissue as lungs and heart [5][6][7]. Others studies have reported lower rates of acute adverse effects from hypofractionated radiotherapy [8,9]. The UK National Institute for Clinical Excellence (NICE) guidelines have recommended hypofractionated dose of 40 Gy in 15 fractions over 3 weeks for adjuvant radiotherapy to the breast only or to the breast plus regional nodes for women with early breast cancer [10,11].…”
Section: Introductionmentioning
confidence: 99%